(untitled) (Journal of Universal Science Research, 2024)
The homeland of bees is South Asia. It is now distributed from the southern latitudes to the Far North. Bees live mainly as a family. One family consists of one mother (also called "king" in the vernacular), several thousand workers and several hundred male bees. Mother bees have a body length of 20-25 mm, a weight of 200-250 mg, lay eggs from spring to autumn, and so on. The wing covers half of the body, nectar, differs by the load on the pollen collector. The reproductive organs of mother bees are well developed. Lives up to 5 years (mothers of experienced beekeepers renew every two years). It lays 2 to 2.5 thousand eggs a day. Worked bees hatch from hatched eggs at 21 days, and male bees hatch from un hatched eggs at 24 days.